A rubber composition for shock absorber top rubber and preparation method thereof

By optimizing the composition ratio of the rubber composition for top rubber for shock absorbers, including modified grafted carbon nanotube composites and nanofillers, the problem of easy aging of existing top rubber materials is solved, significantly improving mechanical properties and aging resistance, and extending the service life of the shock absorbers.

CN119060420BActive Publication Date: 2025-04-01ZHEJIANG HONGLI AUTO PARTS GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411330657.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-04-01
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing shock absorber top glue material is prone to aging, resulting in reduced mechanical properties and reduced shock absorption performance, and the inability to sustainably and effectively shock absorption.

Method used

A rubber composition for top rubber of shock absorber is adopted, and its components include natural rubber, neoprene, zinc oxide, stearic acid, modified grafted carbon nanotube composite, nanofiller, carbon black, sorbitan monostearate, calcium sulfate whiskers, vulcanizer and nanoconcave and concave rod soil, etc., by optimizing the dosage ratio of these components, the aging resistance of the rubber composition is improved.

Benefits of technology

The mechanical properties and aging resistance of the rubber composition for the top rubber of the shock absorber are significantly improved, the service life of the shock absorber is extended, and the problem of shortening the life of the shock absorber due to aging is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119060420B_ABST
    Figure CN119060420B_ABST
Patent Text Reader

Abstract

The invention discloses a rubber composition for a shock absorber top glue and a preparation method thereof, and relates to the technical field of rubber compositions. The rubber composition comprises the following ingredients: natural rubber, chloroprene rubber, zinc oxide, stearic acid, a modified grafted carbon nanotube composite, nano filler, carbon black, sorbitan monostearate, calcium sulfate whisker, a vulcanizing agent, nano attapulgite, and an accelerator. The invention introduces nano fillers, which can not only play an obvious reinforcing role on the rubber, but also improve the aging resistance of the rubber composition for the shock absorber top glue to a certain extent, because the introduced nano titanium dioxide and nano aluminum oxide are matched in a specific ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber compositions, in particular to a rubber composition for a shock absorber top rubber and a preparation method thereof. Background Art

[0002] With the sustained growth of the national economy, the continuous increase in residents' income, the increasingly improved infrastructure, the accelerated urbanization process and the strong support of industrial policies, the demand for automobile consumption has a large room for growth. As residents' income continues to increase, it has further driven the upgrading of residents' consumption, and travel has become more frequent, which will lead to an increasing demand for automobiles.

[0003] Automobile shock absorber is an important component of automobile, and it is also an indispensable part of automobile. Therefore, automobile shock absorber is directly related to the comfort, flexibility and service life of automobile driving, making the car more stable during driving, especially high-speed driving. Shock absorber mainly absorbs the impact generated by the car during driving through elastic vibration. However, frequent work will also damage the shock absorber and shorten its service life. The shock absorber top glue plays an important role as the spring base at the top of the shock absorber assembly. The shock absorber top glue material is directly related to the service life of the entire shock absorber. The existing shock absorber top glue material is easy to age, and the mechanical properties of the aged shock absorber top glue material will be greatly reduced, which will cause the shock absorbing performance of the shock absorber to be significantly reduced, resulting in the inability to maintain a continuous shock absorbing effect on the car.

[0004] Based on this, a rubber composition for a shock absorber top rubber and a preparation method thereof are provided to solve the existing technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a rubber composition for a shock absorber top rubber and a preparation method thereof, so as to solve the deficiencies in the prior art.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A rubber composition for shock absorber top rubber, comprising the following components in parts by weight:

[0008] 100-110 parts by weight of natural rubber, 15-20 parts by weight of chloroprene rubber, 4-6 parts by weight of zinc oxide, 0.2-0.8 parts by weight of stearic acid, 1-3 parts by weight of modified grafted carbon nanotube composite, 1-5 parts by weight of nano filler, 40-50 parts by weight of carbon black, 5-10 parts by weight of sorbitan monostearate, 3-8 parts by weight of calcium sulfate whisker, 2-3 parts by weight of vulcanizing agent, 15-20 parts by weight of nano attapulgite and 1.5-3 parts by weight of accelerator.

[0009] As a further technical solution: the preparation method of the modified grafted carbon nanotube composite is:

[0010] (1) First, carbon nanotubes and nano-bentonite are sequentially added to an ethanol solution, subjected to ultrasonic treatment for 10-15 minutes, and then filtered, washed with water, and dried at 75° C. to obtain a mixture;

[0011] Wherein, the mass fraction of ethanol solution is 20%;

[0012] (2) N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane, and maleic anhydride are mixed together in sequence, heated to 145° C., stirred and reacted for 2 hours, and then cooled to room temperature to obtain a reaction mixture;

[0013] The obtained reaction mixture was added to the ethanol solution and stirred for 40 minutes to obtain a modified solution;

[0014] Among them, the mass fraction of ethanol solution is 90%;

[0015] (3) The mixture obtained in step (1) and the modified liquid are added to the reaction kettle in sequence, and then vacuumed, the temperature is adjusted to 85-90° C., stirred for reaction for 4 hours, and then discharged, cooled, filtered, washed, and vacuum dried to obtain a modified grafted carbon nanotube composite.

[0016] As a further technical solution: the mixing ratio of the carbon nanotubes, nano-bentonite and ethanol solution in step (1) is 10g:3-5g:200mL respectively.

[0017] As a further technical solution: in step (2), the mass ratio of N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride is 5:1-2:1;

[0018] The mixing ratio of the reaction mixture and the ethanol solution is 15-20 g:150 mL.

[0019] As a further technical solution: in step (3), the mixing ratio of the mixed material to the modified liquid is 12-18 g: 200 mL;

[0020] The vacuuming is to evacuate to a vacuum degree of 0.1 Pa;

[0021] The vacuum drying temperature is 55° C. and the time is 2 hours.

[0022] As a further technical solution: the carbon black is N330 carbon black.

[0023] As a further technical solution: the accelerator is accelerator DM;

[0024] The vulcanizing agent is sulfur.

[0025] As a further technical solution: the nanofiller is:

[0026] It is a mixture of nano titanium dioxide and nano aluminum oxide;

[0027] Among them, the mixing mass ratio of nano titanium dioxide and nano aluminum oxide is 3:1.

[0028] A method for preparing a rubber composition for a shock absorber top rubber comprises:

[0029] (1) using an internal mixer to perform internal mixing of natural rubber and chloroprene rubber to obtain a mixed preliminary rubber material;

[0030] (2) mixing the mixed preliminary rubber obtained in step (1) with zinc oxide, stearic acid, and half of the modified grafted carbon nanotube composite, and kneading for the first time to obtain a primary mixed rubber;

[0031] (3) adding the remaining half of the modified grafted carbon nanotube composite, nanofiller, carbon black, sorbitan monostearate, calcium sulfate whisker, and nano-attapulgite to the primary mixed rubber obtained in step (2) for a second mixing to obtain a secondary mixed rubber;

[0032] (4) adding a vulcanizing agent and an accelerator to the secondary mixed rubber obtained in step (3) to perform a third mixing treatment to obtain a final mixed rubber.

[0033] As a further technical solution: after mixing to 140-150°C, discharge the material and leave it for 15-20 hours after discharge;

[0034] The process parameters of the first mixing are: mixing temperature is 150-160℃, mixing time is 6-8min;

[0035] The process parameters of the second mixing are: mixing temperature is 120-140°C, mixing time is 3-5min;

[0036] The process parameters of the third mixing are: mixing temperature is 110-118°C, and mixing time is 25-30min.

[0037] Since light irradiation is one of the causes of rubber aging, especially ultraviolet rays contained in light, which are the most destructive to rubber. In order to delay the aging process of the rubber composition for shock absorber top glue and improve the aging resistance of the shock absorber top glue, the present invention optimizes the components of the rubber composition for shock absorber top glue on a large scale and optimizes the dosage ratio of each component accordingly, so that the mechanical properties and aging resistance of the rubber composition for shock absorber top glue are improved to varying degrees, so that the service life of the shock absorber top glue can be significantly improved, avoiding the problem of shortening the life of the shock absorber due to aging.

[0038] The invention adds natural rubber and chloroprene rubber in a certain amount, and the combined use of the two can improve the oil resistance and weather resistance of the natural rubber to a certain extent, and at the same time can improve the tear resistance and flex resistance of the chloroprene rubber, thereby achieving the effect of improving advantages and complementing disadvantages.

[0039] Beneficial effects:

[0040] The invention not only plays a significant reinforcing role on the rubber by introducing nano fillers, but also can improve the aging resistance of the rubber composition for the shock absorber top rubber to a certain extent because the introduced nano titanium dioxide and nano aluminum oxide are matched in a specific ratio. This is because the wavelength of ultraviolet rays in natural light is mainly 300-400nm, and the nano titanium dioxide and nano aluminum oxide in a specific mass ratio of the invention can absorb a certain amount of ultraviolet light. Under the combination of the specific mass ratio, after the ultraviolet light irradiates the combined nano particles, the outer electrons in the nano particles are excited and jump from the valence band to the conduction band, so that the nano particles can produce a strong The function of absorbing ultraviolet light can improve the light aging resistance of the rubber composition for shock absorbers to a certain extent. In order to further significantly improve the aging resistance of the rubber composition for shock absorbers, the present invention introduces a modified grafted carbon nanotube composite, which can significantly improve the heat aging resistance and ozone aging resistance of the rubber composition for shock absorber top glue, and further complements the various aging resistance of the rubber composition for shock absorber top glue. Compared with conventional carbon nanotubes, the introduction of the modified grafted carbon nanotube composite of the present invention will promote the conduction and flow speed of heat between the natural rubber network during the vulcanization process, thereby improving the vulcanization efficiency and improving the vulcanization performance.

[0041] The rubber composition for the shock absorber top glue prepared by the present invention mainly hinders the movement of molecular chains through the interaction between molecules, which will form a phenomenon that stress and strain are not parallel, and then will show a strong viscoelastic damping characteristic. The shock absorber top glue prepared in this way can help the shock absorber reduce the impact it receives, and can reduce the fatigue damage caused to itself under frequent impacts, thereby extending the working life of the shock absorber. In addition, by greatly improving the aging resistance, it can effectively delay the aging process, thereby reducing the process of shortening the life of the shock absorber due to aging. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a bar graph of tensile strength of embodiments and comparative examples. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] A rubber composition for shock absorber top rubber is processed according to the following dosage:

[0046] 100kg natural rubber, 15kg chloroprene rubber, 4kg zinc oxide, 0.2kg stearic acid, 1kg modified grafted carbon nanotube composite, 1kg nanofiller, 40kg N330 carbon black, 5kg sorbitan monostearate, 3kg calcium sulfate whisker, 2kg sulfur, 15kg nano-attapulgite, 1.5kg accelerator DM. The nanofiller is:

[0047] It is a mixture of nano titanium dioxide and nano aluminum oxide;

[0048] Among them, the mixing mass ratio of nano titanium dioxide and nano aluminum oxide is 3:1.

[0049] The preparation method of the modified grafted carbon nanotube composite is as follows:

[0050] (1) First, carbon nanotubes and nano-bentonite are sequentially added to an ethanol solution, subjected to ultrasonic treatment for 12 minutes, and then filtered, washed with water, and dried at 75° C. to obtain a mixture;

[0051] The mass fraction of the ethanol solution is 20%; the mixing ratios of the carbon nanotubes, nano-bentonite and the ethanol solution are 10g:3g:200mL, respectively.

[0052] (2) N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane, and maleic anhydride are mixed together in sequence, heated to 145° C., stirred and reacted for 2 hours, and then cooled to room temperature to obtain a reaction mixture;

[0053] The obtained reaction mixture was added to the ethanol solution and stirred for 40 minutes to obtain a modified solution;

[0054] The mass fraction of the ethanol solution is 90%; the mass ratio of N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride is 5:1:1;

[0055] The mixing ratio of the reaction mixture and the ethanol solution is 15g:150mL.

[0056] (3) The mixture obtained in step (1) and the modified liquid are added to the reaction kettle in sequence, and then vacuumed, the temperature is adjusted to 85°C, stirred for reaction for 4 hours, and then discharged, cooled, filtered, washed, and vacuum dried to obtain a modified grafted carbon nanotube composite; the mixing ratio of the mixture to the modified liquid is 12g:200mL; the vacuuming is to 0.1Pa; the vacuum drying temperature is 55°C and the time is 2 hours.

[0057] Example 2

[0058] A rubber composition for shock absorber top rubber is processed according to the following dosage:

[0059] 102kg natural rubber, 16kg chloroprene rubber, 4.5kg zinc oxide, 0.3kg stearic acid, 1.5kg modified grafted carbon nanotube composite, 2kg nanofiller, 44kg N330 carbon black, 6kg sorbitan monostearate, 4kg calcium sulfate whisker, 2.5kg sulfur, 18kg nano-attapulgite, 1.8kg accelerator DM. The nanofiller is:

[0060] It is a mixture of nano titanium dioxide and nano aluminum oxide;

[0061] Among them, the mixing mass ratio of nano titanium dioxide and nano aluminum oxide is 3:1.

[0062] The preparation method of the modified grafted carbon nanotube composite is as follows:

[0063] (1) First, carbon nanotubes and nano-bentonite are sequentially added to an ethanol solution, subjected to ultrasonic treatment for 12 minutes, and then filtered, washed with water, and dried at 75° C. to obtain a mixture;

[0064] The mass fraction of the ethanol solution is 20%; the mixing ratios of the carbon nanotubes, nano-bentonite and the ethanol solution are 10g:4g:200mL, respectively.

[0065] (2) N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane, and maleic anhydride are mixed together in sequence, heated to 145° C., stirred and reacted for 2 hours, and then cooled to room temperature to obtain a reaction mixture;

[0066] The obtained reaction mixture was added to the ethanol solution and stirred for 40 minutes to obtain a modified solution;

[0067] The mass fraction of the ethanol solution is 90%; the mass ratio of N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride is 5:1.2:1;

[0068] The mixing ratio of the reaction mixture and the ethanol solution is 18g:150mL.

[0069] (3) The mixture obtained in step (1) and the modified liquid are added to the reaction kettle in sequence, and then vacuumed, the temperature is adjusted to 88°C, stirred for reaction for 4 hours, and then discharged, cooled, filtered, washed, and vacuum dried to obtain a modified grafted carbon nanotube composite; the mixing ratio of the mixture to the modified liquid is 15g:200mL; the vacuuming is performed to a vacuum degree of 0.1Pa; the vacuum drying temperature is 55°C and the time is 2 hours.

[0070] Example 3

[0071] A rubber composition for shock absorber top rubber is processed according to the following dosage:

[0072] 106kg natural rubber, 18kg chloroprene rubber, 5kg zinc oxide, 0.5kg stearic acid, 2kg modified grafted carbon nanotube composite, 3kg nanofiller, 44kg N330 carbon black, 8kg sorbitan monostearate, 5kg calcium sulfate whisker, 2.5kg sulfur, 18kg nano-attapulgite, 2kg accelerator DM. The nanofiller is:

[0073] It is a mixture of nano titanium dioxide and nano aluminum oxide;

[0074] Among them, the mixing mass ratio of nano titanium dioxide and nano aluminum oxide is 3:1.

[0075] The preparation method of the modified grafted carbon nanotube composite is as follows:

[0076] (1) First, carbon nanotubes and nano-bentonite are sequentially added to an ethanol solution, ultrasonically treated for 14 minutes, and then filtered, washed with water, and dried at 75° C. to obtain a mixture;

[0077] The mass fraction of the ethanol solution is 20%; the mixing ratios of the carbon nanotubes, nano-bentonite and the ethanol solution are 10g:4g:200mL, respectively.

[0078] (2) N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane, and maleic anhydride are mixed together in sequence, heated to 145° C., stirred and reacted for 2 hours, and then cooled to room temperature to obtain a reaction mixture;

[0079] The obtained reaction mixture was added to the ethanol solution and stirred for 40 minutes to obtain a modified solution;

[0080] The mass fraction of the ethanol solution is 90%; the mass ratio of N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride is 5:1.5:1;

[0081] The mixing ratio of the reaction mixture and the ethanol solution is 19g:150mL.

[0082] (3) The mixture obtained in step (1) and the modified liquid are added to the reaction kettle in sequence, and then vacuumed, the temperature is adjusted to 88°C, stirred for reaction for 4 hours, and then discharged, cooled, filtered, washed, and vacuum dried to obtain a modified grafted carbon nanotube composite; the mixing ratio of the mixture to the modified liquid is 16g:200mL; the vacuuming is to 0.1Pa; the vacuum drying temperature is 55°C and the time is 2 hours.

[0083] Example 4

[0084] A rubber composition for shock absorber top rubber is processed according to the following dosage:

[0085] 108kg natural rubber, 16kg chloroprene rubber, 5kg zinc oxide, 0.4kg stearic acid, 2.4kg modified grafted carbon nanotube composite, 4kg nanofiller, 46kg N330 carbon black, 8kg sorbitan monostearate, 5kg calcium sulfate whisker, 2.5kg sulfur, 18kg nano-attapulgite, 2kg accelerator DM. The nanofiller is:

[0086] It is a mixture of nano titanium dioxide and nano aluminum oxide;

[0087] Among them, the mixing mass ratio of nano titanium dioxide and nano aluminum oxide is 3:1.

[0088] The preparation method of the modified grafted carbon nanotube composite is as follows:

[0089] (1) First, carbon nanotubes and nano-bentonite are sequentially added to an ethanol solution, subjected to ultrasonic treatment for 12 minutes, and then filtered, washed with water, and dried at 75° C. to obtain a mixture;

[0090] The mass fraction of the ethanol solution is 20%; the mixing ratios of the carbon nanotubes, nano-bentonite and the ethanol solution are 10g:4g:200mL, respectively.

[0091] (2) N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane, and maleic anhydride are mixed together in sequence, heated to 145° C., stirred and reacted for 2 hours, and then cooled to room temperature to obtain a reaction mixture;

[0092] The obtained reaction mixture was added to the ethanol solution and stirred for 40 minutes to obtain a modified solution;

[0093] The mass fraction of the ethanol solution is 90%; the mass ratio of N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride is 5:1.5:1;

[0094] The mixing ratio of the reaction mixture and the ethanol solution is 15-20 g:150 mL.

[0095] (3) The mixture obtained in step (1) and the modified liquid are added to the reaction kettle in sequence, and then vacuumed, the temperature is adjusted to 88°C, stirred for reaction for 4 hours, and then discharged, cooled, filtered, washed, and vacuum dried to obtain a modified grafted carbon nanotube composite; the mixing ratio of the mixture to the modified liquid is 15g:200mL; the vacuuming is performed to a vacuum degree of 0.1Pa; the vacuum drying temperature is 55°C and the time is 2 hours.

[0096] Example 5

[0097] A rubber composition for shock absorber top rubber is processed according to the following dosage:

[0098] 110kg natural rubber, 20kg chloroprene rubber, 6kg zinc oxide, 0.8kg stearic acid, 3kg modified grafted carbon nanotube composite, 5kg nanofiller, 50kg N330 carbon black, 10kg sorbitan monostearate, 8kg calcium sulfate whisker, 3kg sulfur, 20kg nano-attapulgite, 3kg accelerator DM. The nanofiller is:

[0099] It is a mixture of nano titanium dioxide and nano aluminum oxide;

[0100] Among them, the mixing mass ratio of nano titanium dioxide and nano aluminum oxide is 3:1.

[0101] The preparation method of the modified grafted carbon nanotube composite is as follows:

[0102] (1) First, carbon nanotubes and nano-bentonite are sequentially added to an ethanol solution, subjected to ultrasonic treatment for 15 minutes, and then filtered, washed with water, and dried at 75° C. to obtain a mixture;

[0103] The mass fraction of the ethanol solution is 20%; the mixing ratios of the carbon nanotubes, nano-bentonite and the ethanol solution are 10g:5g:200mL, respectively.

[0104] (2) N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane, and maleic anhydride are mixed together in sequence, heated to 145° C., stirred and reacted for 2 hours, and then cooled to room temperature to obtain a reaction mixture;

[0105] The obtained reaction mixture was added to the ethanol solution and stirred for 40 minutes to obtain a modified solution;

[0106] The mass fraction of the ethanol solution is 90%; the mass ratio of N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride is 5:2:1;

[0107] The mixing ratio of the reaction mixture and the ethanol solution is 20g:150mL.

[0108] (3) The mixture obtained in step (1) and the modified liquid are added to the reaction kettle in sequence, and then vacuumed, the temperature is adjusted to 90°C, stirred for reaction for 4 hours, and then discharged, cooled, filtered, washed, and vacuum dried to obtain a modified grafted carbon nanotube composite; the mixing ratio of the mixture to the modified liquid is 18g:200mL; the vacuuming is performed to a vacuum degree of 0.1Pa; the vacuum drying temperature is 55°C and the time is 2 hours.

[0109] Examples 1-5 are all prepared by the following method:

[0110] A method for preparing a rubber composition for a shock absorber top rubber comprises:

[0111] (1) Using an internal mixer to perform internal mixing of natural rubber and chloroprene rubber, a preliminary mixed rubber material is obtained after internal mixing, and the material is discharged after internal mixing at 145°C, and the material is left for 20 hours after discharge;

[0112] (2) mixing the mixed preliminary rubber obtained in step (1) with zinc oxide, stearic acid, and half of the modified grafted carbon nanotube composite, and kneading for the first time to obtain a primary mixed rubber; the process parameters of the first mixing are: mixing temperature of 152° C., mixing time of 7 min;

[0113] (3) adding the remaining half of the modified grafted carbon nanotube composite, nanofiller, carbon black, sorbitan monostearate, calcium sulfate whisker, and nano-attapulgite to the first mixed rubber obtained in step (2) for a second mixing to obtain a second mixed rubber. The process parameters for the second mixing are: mixing temperature of 126° C., mixing time of 4 min;

[0114] (4) adding a vulcanizing agent and an accelerator to the secondary mixed rubber obtained in step (3) for a third mixing treatment to obtain a final mixed rubber; the process parameters of the third mixing are: a mixing temperature of 115° C. and a mixing time of 25 min.

[0115] Comparative Example 1:

[0116] On the basis of Example 1, the modified grafted carbon nanotube composite was replaced with an equal amount of carbon nanotubes, and the rest of the technical solutions remained unchanged.

[0117] test:

[0118] Physical properties of the embodiments and comparative examples were tested: tensile properties were tested according to GB / T528-2009;

[0119] Table 1

[0120] Tensile strength MPa Elongation at break % Example 1 31.0 851 Example 2 31.5 855 Example 3 32.2 860 Example 4 31.3 852 Example 5 31.9 857 Comparative Example 1 28.4 786

[0121] It can be seen from Table 1 that the rubber composition for shock absorber top glue prepared by the present invention has higher tensile properties. When conventional carbon nanotubes are used, the tensile properties of the rubber composition for shock absorber top glue obviously decrease to a certain extent. This is because the introduction of conventional carbon nanotubes into the rubber composition for shock absorber top glue will cause uneven dispersion due to the agglomeration effect, which will affect the mechanical properties of the rubber composition for shock absorber top glue.

[0122] The hot air aging test was carried out on the embodiments and comparative examples: the sample size was 100 mm × 8 mm × 2 mm;

[0123] According to GB / T3512-2001, the aging condition is 100℃×24h;

[0124] Table 2

[0125]

[0126] It can be seen from Table 2 that the rubber composition for shock absorber top rubber prepared in the present invention has excellent heat aging resistance.

[0127] Ozone aging test was performed on the embodiments and comparative examples:

[0128] According to GB / T7762-2014, the sample size is 100mm×8mm×2mm, the static tensile rate is 20%, the temperature is 35℃, the time is 72h, and the ozone mass fraction is 55.0×10 -8 ;

[0129] Table 3

[0130] Ozone aging Example 1 No abnormality found Example 2 No abnormality found Example 3 No abnormality found Example 4 No abnormality found Example 5 No abnormality found Comparative Example 1 Micro cracks on the surface

[0131] It can be seen from Table 3 that the rubber composition for shock absorber top glue prepared by the present invention has excellent ozone aging resistance. Compared with conventional carbon nanotubes, the introduction of the modified grafted carbon nanotube composite of the present invention can effectively improve the ozone aging resistance of the rubber composition for shock absorber top glue.

[0132] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A rubber composition for a shock absorber top rubber, characterized in that: The following ingredients are included by weight: 100-110 parts by weight of natural rubber, 15-20 parts by weight of chloroprene rubber, 4-6 parts by weight of zinc oxide, 0.2-0.8 parts by weight of stearic acid, 1-3 parts by weight of modified grafted carbon nanotube composite, 1-5 parts by weight of nano filler, 40-50 parts by weight of carbon black, 5-10 parts by weight of sorbitan monostearate, 3-8 parts by weight of calcium sulfate whisker, 2-3 parts by weight of vulcanizing agent, 15-20 parts by weight of nano attapulgite, and 1.5-3 parts by weight of accelerator; The modified grafted carbon nanotube composite preparation method is: (1) First, carbon nanotubes and nano-bentonite are added to an ethanol solution in sequence, and ultrasonically treated for 10-15 minutes, and then filtered, washed with water, and dried at 75°C to obtain a mixture; Among them, the mass fraction of ethanol solution is 20%; (2) N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride are mixed together in sequence, heated to 145° C., stirred and reacted for 2 hours, and then cooled to room temperature to obtain a reaction mixture; The obtained reaction mixture was added to the ethanol solution and stirred for 40 minutes to obtain a modified solution; Among them, the mass fraction of ethanol solution is 90%; (3) The mixture obtained in step (1) and the modified liquid are added to the reaction kettle in sequence, and then vacuumed, the temperature is adjusted to 85-90°C, stirred and reacted for 4 hours, and then discharged, cooled, filtered, washed, and vacuum dried to obtain a modified grafted carbon nanotube composite; The mixing ratio of the carbon nanotubes, nano-bentonite and ethanol solution in step (1) is 10 g: 3-5 g: 200 mL respectively; In step (2), the mass ratio of N-phenyl-p-phenylenediamine, γ-(meth)acryloxypropyldimethylbenzyloxysilane and maleic anhydride is 5:1-2:1; The mixing ratio of the reaction mixture and the ethanol solution is 15-20 g: 150 mL; In step (3), the mixing ratio of the mixed material to the modified liquid is 12-18 g: 200 mL; The vacuuming is to evacuate to a vacuum degree of 0.1 Pa; The vacuum drying temperature is 55°C and the time is 2 hours; The carbon black is N330 carbon black; The accelerator is accelerator DM; The vulcanizing agent is sulfur; The nanofiller is: It is a mixture of nano titanium dioxide and nano aluminum oxide; Among them, the mixing mass ratio of nano titanium dioxide and nano aluminum oxide is 3:

1.

2. The method for preparing a rubber composition for a shock absorber top rubber according to claim 1, characterized in that: include: (1) Using an internal mixer to perform internal mixing treatment on natural rubber and chloroprene rubber, and obtaining a mixed preliminary rubber material after internal mixing treatment; (2) mixing the preliminary mixed rubber obtained in step (1) with zinc oxide, stearic acid, and half of the modified grafted carbon nanotube composite, and kneading for the first time to obtain a primary mixed rubber; (3) adding the remaining half of the modified grafted carbon nanotube composite, nanofiller, carbon black, sorbitan monostearate, calcium sulfate whisker, and nano-attapulgite to the first mixed rubber obtained in step (2) for a second mixing to obtain a second mixed rubber; (4) Adding a vulcanizing agent and an accelerator to the secondary mixed rubber obtained in step (3) for a third mixing treatment to obtain a final mixed rubber.

3. The method for preparing a rubber composition for a shock absorber top rubber according to claim 2, characterized in that: After mixing to 140-150℃, discharge the material and leave it for 15-20 hours; The process parameters of the first mixing are: mixing temperature is 150-160℃, mixing time is 6-8min; The process parameters of the second mixing are: mixing temperature is 120-140°C, mixing time is 3-5min; The process parameters of the third mixing are: mixing temperature is 110-118°C, and mixing time is 25-30min.

Citation Information

Patent Citations

  • High-performance windshield wiper rubber strip containing carbon nanotubes, and preparation method thereof

    CN111004417A